PRESCHOOL EDUCATION ORGANIZATION AND FAMILY COOPERATION - Toshmatova Zamira Jumanovna (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the pedagogical factors of employees of preschool education organizations are discussed and recommendations are made to find ways to further improve the family upbringing of children of preschool age, to find ways to further improve cooperation with parents, to strengthen the connection between family education and social education.